Städtische Kommunikation in den Kanzleien des Mittelalters und der Frühen Neuzeit = Komunikacja językowa w kancelariach miejskich średniowiecza i wczesnej nowożytności = Urban communications in the chancelleries of the Middle Ages and the early modern period - Biszczanik, Marek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The city chancelleries of the late Middle Ages and the beginning of the early modern period can be regarded as a supporting factor in the development of Early New High German as well as of the then forms of everyday communication, both written and spoken.
Keywords: język wczesno-nowo-wysoko-niemiecki; Śląsk; dialekt śląski; język kancelaryjny; komunikacja językowa; język mówiony; język pisany; Early New High German; Silesia; Silesian dialect; chancellery language; language communication; spoken language; written language